Development Of Arduino System For Cylinder Deactivation Strategy In Perodua Myvi Sxi K3-Ve Engine - Abas, Noor Affandy (2020)
Cylinder deactivation (CDA) is one of the fuel efficiency strategy that offer lower fuel consumption and exhaust emissions by allowing the multi-cylinder gasoline engine to run with smaller engine displacements at lower engine loads and speeds. Deactivating engine cylinders is really a challenging task. The cylinder deactivation system (CDS) should not only cut off the fuel injection but also account for the intake air associated with the induction stroke. Therefore, each firing cylinder needs more air by opening the throttle to give higher intake manifold pressures, which reduce the pumping loss of the engine. The objective in this study is to investigate the effect of normal engine problem associated with cylinder deactivation. Then, a development of manual CDA into CDS for fuel and emission improvement will take place and finally their effectiveness in term of fuel and emission will be accessed. A relay-based control system capable of deactivating the individual cylinder was built to investigate the effect on the engine performance and the engine stability at lower displacements. Thus, a controller named CDS using the Arduino microcontroller was designed for controlling cylinder deactivation using the skip fire cycle methodology. With the Arduino system, the engine cylinders were selectively deactivated based on a control strategy and were examined over a driving cycle without being loaded. A cost-effective CDS is implemented without cutting off the intake air by relocating the oxygen sensor at the exhaust runner. A racing-style 4-2-1 exhaust manifold was incorporated to a 1.3-liter, four-cylinder inline K3-VE gasoline engine, to improve engine breathing and performance at lower engine speeds. The significance of this study is the development of a manual CDA into a CDS for a small 1.3 liter four-cylinder inline engine base on the requirement for the UTeM Perodua Eco-Challenge 2013 (PEC2013). The results show that the effect of CDS control strategy are very significant to reduce the pumping losses, thus gives an improvement up to 8.13 percent in the average fuel consumption and CO2 reduction up to 5.7 percent while HC up to 6.7 percent especially at around 56 Nm torque and 50 percent of the speed during low load operation. The critical improvement of this study is the effectiveness of the developed cost-effective CDS using Arduino platform and an excellent performance of cylinder deactivation in terms of fuel consumption and exhaust emissions. The developed system also allowed UTeM Perodua Eco Challenge 2013 team to win second place in PEC2013 competition with the longest distance travelled of 12.97 km per liter. Therefore, the outcome of this study shows the excellent performance of CDS in improving fuel consumption and emissions for Perodua Myvi K3-VE engine. It also provides some insight on deactivation strategies to design a microcontroller with integration of process signal sensor data and control system. The measurements show the improvements in fuel consumption and exhaust emissions at the expense of minimal engine power loss and vibration which would be beneficial for future engine CDS development.